Nanofiber-boosted retrograded starch/pectin microparticles for targeted 5-Aminosalicylic acid delivery in inflammatory bowel disease: In vitro and in vivo non-toxicity evaluation - Meneguin, Andréia Bagliotti [UNESP]; Roque-Borda, Cesar Augusto; Piperas, Ana Beatriz Grotto [UNESP]; Pollini, Maria Fernanda Ortolani [UNESP]; Cardoso, Vinicius Martinho Borges [UNESP]; Primo, Laura Maria Duran Gleriani [UNESP]; Alemi, Forogh [UNESP]; Pavan, Fernando Rogério [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2024)
Incorporating 5-aminosalicylic acid (5-ASA) into a colon-specific carrier is crucial for treating inflammatory bowel diseases (IBD), as it enhances therapeutic efficacy, targets the affected regions directly, and minimizes side effects. This study evaluated the impact of incorporating cellulose nanofibers (CNF) on the in vitro and in vivo biological performance of retrograded starch/pectin (RS/P) microparticles (MPs) containing 5-ASA. Using Fourier Transform Infrared (FTIR) Spectroscopy, shifts in the spectra of retrograded samples containing CNF were observed with increasing CNF proportions, suggesting the establishment of new supramolecular interactions. Liquid absorption exhibited pH-dependent behaviors, with reduced absorption in simulated gastric fluid (∼269 %) and increased absorption in simulated colonic fluid (∼662 %). Increasing CNF concentrations enhanced mucoadhesion in porcine colonic sections, with a maximum force of 3.4 N at 50 % CNF. Caco-2 cell viability tests showed biocompatibility across all tested concentrations (0.0625–2.0000 mg/mL). Evaluation of intestinal permeability in Caco-2 cell monolayers demonstrated up to a tenfold increase in 5-ASA permeation, ranging from 29 % to 48 %. An in vivo study using Galleria mellonella larvae, with inflammation induced by LPS, showed reduction of inflammation. Given the scalability of spray-drying, these findings suggest the potential of CNF-incorporated RS/P microparticles for targeted 5-ASA delivery in IBD.
Keywords: 5-ASA; Cellulose nanofibers; Colon-specific delivery; Inflammatory bowel disease; Microparticles